Analisis Dampak Kecanduan Media Sosial terhadap Kesehatan Mental Remaja di Kalangan Generasi Z di UNIMED - Dalimunthe, Syairal Fahmy; Nasution, Henny Puspa Hendrani; Hawari, Mhd Fadhlan; Alhadi, M. Raflie; Silalahi, Yohanes Febrian; Perangin Angin, Yosa Steven (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
This study aims to explore the impact of social media addiction on the mental health of Generation Z adolescents at Universitas Negeri Medan (UNIMED). Using a qualitative approach through literature review and in-depth interviews, this research involved three students from the Faculty of Economics, Faculty of Mathematics and Natural Sciences, and Faculty of Sport Science as respondents. The research findings show that UNIMED students spend more than 4 hours every day using social media such as Instagram, TikTok, Twitter, Facebook, YouTube, Telegram, and WhatsApp. This excessive use of social media has a negative impact on three main aspects: (1) psychological health, which includes notification stress and a tendency to overthink, (2) social interaction, where face-to-face communication becomes less quality and awkward, and (3) mental health, including disturbed sleep patterns, anxiety, and emotional exhaustion. This study also found that although social media makes communication easier, its uncontrolled use can damage the mental well-being of Generation Z students at UNIMED.